2016
DOI: 10.3847/1538-4357/833/2/263
|View full text |Cite
|
Sign up to set email alerts
|

Herschel Observations of Dusty Debris Disks

Abstract: We present results from two Herschel observing programs using the Photodetector Array Camera and Spectrometer. During three separate campaigns, we obtained Herschel data for 24 stars at 70, 100, and 160 µm. We chose stars that were already known or suspected to have circumstellar dust based on excess infrared emission previously measured with IRAS or Spitzer, and used Herschel to examine long-wavelength properties of the dust. Fifteen stars were found to be uncontaminated by background sources, and possess inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 77 publications
0
19
2
Order By: Relevance
“…In July 2011 and January 2012, the Herschel Space Observatory used its Photodetector Array Camera and Spectrometer (PACS) to measure BD +20 307 at 70 and 100 µm. The reported 70 µm flux density of 47 ± 3 mJy (Vican et al 2016) is substantially larger than that reported with MIPS from 2007 of 28.6 ± 1.9 mJy (Weinberger et al 2011).…”
Section: Previous Observationscontrasting
confidence: 70%
“…In July 2011 and January 2012, the Herschel Space Observatory used its Photodetector Array Camera and Spectrometer (PACS) to measure BD +20 307 at 70 and 100 µm. The reported 70 µm flux density of 47 ± 3 mJy (Vican et al 2016) is substantially larger than that reported with MIPS from 2007 of 28.6 ± 1.9 mJy (Weinberger et al 2011).…”
Section: Previous Observationscontrasting
confidence: 70%
“…Allowing for the superheat ratio T obs /T BB = 100K/71K = 1.41 found by NIRDS for dust in the HR 4796A (A0.5V) ring at ~75 AU from its primary (Lisse et al 2017) moves this location out to ~40 AU, closer to the Curie et al estimate. The remaining discrepancy between the spectral and imaging radial distance estimates might be due to our poor current characterization of the MIR-FIR SED peak; to our lack of understanding of the superheat behavior of the HD 36546 outer dust (values of T obs /T BB out to [5][6][7][8][9][10][11][12][13][14][15] have been reported by Rodriguez &Zuckerman 2012 andVican et al 2016) ; or to the different sensitivities of scattered light (∝ surface area*albedo) vs. thermal emission (∝ surface area*emissivity*T 4 ) measurements of circumstellar dust in a thick disk, which will weight closer-in dust thermal emission most highly (c.f. Watson et al 2009 and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…This criterion is certainly met by cool Edgeworth-Kuiper belt analogues, but falls down for stars at an earlier evolutionary phase where planet formation is believed to be ongoing, and where the flux excess tends to peak at mid-IR wavelengths (e.g. Melis et al 2010;Fujiwara et al 2012;Vican et al 2016). The fractional luminosities for the SONS surveys discs are given in Table 3, and all but beam in arcseconds, then the disc radius as specified in Equation 2 will be in astronomical units.…”
Section: Fractional Luminositiesmentioning
confidence: 99%